Komunikasi Interpersonal Pemimpin Redaksi Lembaga Pers Mahasiswa (LPM) Dinamika Universitas Islam Negeri Sumatera Utara Dalam Meningkatkan Kreatif Menulis Dikalangan Mahasiswa - Saputri, Ika Gita; Ritonga, Elfi Yanti (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This study seeks to investigate the impact of the editor-in-chief of LPM Dinamika UIN SU's interpersonal communication on enhancing students' writing originality. The research employed a qualitative method with a qualitative descriptive approach. The researchers at the LPM Dinamika UIN SU secretariat collected data by conducting interviews and participant observation. Data analysis techniques encompass the processes of gathering data, condensing data, presenting data, and deriving conclusions. The research findings demonstrate that the editor-in-chief's interpersonal communication with members plays a significant impact in encouraging and motivating them to enhance their writing originality. The editor-in-chief offers training, disseminates the most up-to-date material, and expresses recognition to members who demonstrate exceptional performance. In addition, social media serves as a significant source of knowledge and a valuable tool for learning. The research findings indicate that the combination of excellent interpersonal communication, environmental support, and utilization of social media can greatly enhance the writing creativity of those involved in campus journalism organizations.